If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3(x-12)=x+8
We simplify the equation to the form, which is simple to understand
2/3(x-12)=x+8
Simplifying:
+ 0.666666666667*(x-12)=x+8
Reorder the terms in parentheses
+( + 0.666666666667x-8)=x+8
Remove unnecessary parentheses
+ 0.666666666667x-8=+x+8
We move all terms containing x to the left and all other terms to the right.
+ 0.666666666667x-1x=+8+8
We simplify left and right side of the equation.
-0.333333333333x=+16
We divide both sides of the equation by -0.333333333333 to get x.
x=-48
| 2.8-0.3m=5 | | x+2x=10 | | 0.5x=x+1 | | (3x+2)(2x^2-5x-3)= | | s^3+t^3=0 | | 5z+7=32 | | 2x^2-25x-13= | | B=1.5(j-26) | | 4x+15=3x+25 | | 48=4(n+4) | | -4x+1=5x-8 | | 9+8n+-3n= | | ab+2a=c | | 4.5-8.1= | | 5(x+1)=3(n+2) | | 1.50x+11=2x+8 | | n^2-4n+4=0 | | 28x^3-6x^2-4x= | | 2x^2-6x-22=0 | | 5x+10x=0 | | 8x-3=6x+15 | | (x-45)(x-45)(x-45)(x-45)=360 | | x=2y+4 | | 12a+3=11a+4 | | -2(y+6)=6y+20 | | a-3b=2c | | 180=(x-45)+x+x | | 2x-9=72 | | (g+a)-3g=1+g | | 5(x+5)=7(x-5) | | X*2+4*X+4=0 | | 3x^3+x^2+18x+6= |